2013
DOI: 10.1155/2013/251603
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the “Streitberger” Needle in a Chinese Population with Acupuncture: A Randomized, Single-Blinded, and Crossover Pilot Study

Abstract: We studied the validity of a “Streitberger” needle as a valid approach in a Chinese population with experience of acupuncture. Volunteers were recruited from students of the School of Acupuncture and Moxibustion, Guangzhou University of Chinese Medicine. Sixty students receiving education in acupuncture theory and experience in practical acupuncture were tested in study determining whether needling with the placebo needle felt any different from conventional acupuncture. Outcomes included measures of penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…In their study, Streitberger et al reported that none of the volunteers suspected that the needle might not have penetrated the skin [ 47 ]. This type of needle has been regarded as a reliable sham control in many studies [ 48 50 ] and produced successful blinding even in Chinese subjects who had prior experience with was estimated based on the acupuncture [ 51 ]. We will use various methods to increase credibility, such as keeping the sham needles out of the patients’ direct view and using 12-mm wide Steri-strip (manufactured by 3 M) and MRI-compatible needles to fix the needle evenly inside the foot, including SP4, in the MRI scanner.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Streitberger et al reported that none of the volunteers suspected that the needle might not have penetrated the skin [ 47 ]. This type of needle has been regarded as a reliable sham control in many studies [ 48 50 ] and produced successful blinding even in Chinese subjects who had prior experience with was estimated based on the acupuncture [ 51 ]. We will use various methods to increase credibility, such as keeping the sham needles out of the patients’ direct view and using 12-mm wide Steri-strip (manufactured by 3 M) and MRI-compatible needles to fix the needle evenly inside the foot, including SP4, in the MRI scanner.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects who entered the control group will receive a placebo acupuncture treatment by using a non-invasive placebo needle50 with the same acupoints as the treatment group. The Streitberger needle has been widely used in clinical research on placebo acupuncture treatment of insomnia,22 51 52 and studies have shown that using this needle in a placebo acupuncture group is reliable for the Chinese population 53. Since the Streitberger needles will be in place for 20 min, they will need to be firmly affixed to the skin or scalp.…”
Section: Methodsmentioning
confidence: 99%
“…For subjects assigned to the control group, Streitberger's non-invasive acupuncture needles (gauge 8 × 1.2″/0.30 × 30 mm) will be applied as a sham control at the same acupoints, which are used in the acupuncture intervention group, as the same stimulation modality, except that the needles are only adhered to the skin by a small plastic ring instead of being inserted [15,16] and the stimulation will be a "pseudo stimulation", which will be given by connecting the needle to an incorrect output socket of the electrical acupuncture stimulation instrument. The credibility and validity of this system has been welldemonstrated [17,18].…”
Section: Sham Acupuncturementioning
confidence: 99%